Analysis of Liquidity and Profitability Ratios for Measuring the Financial Performance of PT Tiki JNE Cikupa in 2021-2023 - Aries Sundoro (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
The times affect the company's financial situation. The level of uncertainty and risk is difficult to measure against company performance. Moreover, the impact of COVID-19 has caused many companies to go bankrupt. However, bankruptcy can also be attributed to unhealthy financial factors and high operating costs. Additionally, management errors in handling finances can lead to a decline in the company's financial performance, often due to insufficient analysis of financial reports, which are essential for evaluating the company and making informed policies. PT Tiki JNE Cikupa is one of the companies in Tangerang Regency that has survived the impact of the COVID-19 pandemic. The purpose of this study is to evaluate the financial performance of PT Tiki JNE Cikupa from 2021 to 2023. This research utilizes a descriptive approach with quantitative analysis tools. Data collection is done through the financial statements of PT Tiki JNE Cikupa. The analysis tool uses financial ratios, namely liquidity, solvency, and profitability. The results of this study indicate that the average liquidity ratios are as follows: the current ratio is 145%, the quick ratio is 145%, and the cash ratio is 108%. For profitability ratios, the gross profit margin and net profit margin are 6%, ROI is 13%, and ROE is 9%. In conclusion, the liquidity and profitability ratios indicate that the financial performance of PT Tiki JNE Cikupa is not good.